Geofísica aplicada à Arqueologia: investigação no Sítio Histórico Engenho Murutucu, em Belém, Pará - MELO, Marina da Silveira e (Universidade Federal do Pará, 2014)
This research sought through geophysical methodology the indication of possible locations of buried remains of occupation and foundations of the old construction of a slave quarter in the Engenho Murutucu, a historical site that has importance and relevance for the history of Pará. Following a magnetic map constructed with data from a previous research, 26 GPR profiles were carried out in the area using a 400 MHz antenna. The investigated depth in the GPR profiles was around 1,75 m. The analysis and correlation of the magnetic and GPR data allowed to reach the purpose of the research. The resulting geophysical indications will guide the future archaeological interventions in the site.